STUDY OF CHRONIC EFFECTS OF VARYING DOSAGE OF X-RAYS ON HEPATOTOXICITY IN WISTAR ALBINO RATS - C, Debajit; K, Reshma; K, Sudha; Chiranth, Chiranth; Rahul, Rahul; Yadav, Charu; Rai, Rajalaxmi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: This study focuses on the chronic effects of various doses of radiation in the liver of albino Wistar rats subjected to irradiation using X-rays. Materials and Methods: In the present study, albino Wistar rats were exposed to various doses of X-rays (4 Gy, 6 Gy, and 6.6 Gy) and the animals were observed for 30 days, following which they were sacrificed and liver tissue, being one of the targets of radiation-induced damage was analyzed for the oxidative stress markers, namely, reduced glutathione (GSH), superoxide dismutase (SOD), catalase and lipid peroxidation indicator, and malondialdehyde (MDA). Histopathological studies of the liver were also performed. Results: Indicated that there was a significant increase in GSH and SOD levels in the animals exposed to radiation compared to controls (p<0.05). A decrease in these values was observed at 6.6 Gy compared to 6 Gy which was non-significant. However, there was a significant and consistent decrease in catalase and a similar increase in MDA with increased doses of X rays (p<0.05). Damage in hepatic structural architecture and disruption of central vein correlated positively with increased doses of X rays. Conclusion: Our study strongly supports the hypothesis of the involvement of free radicals in radiation-induced damage to living systems.